Comparison of CT only contour with MRI guided contouring in external beam radiotherapy for carcinoma rectum - Rani, Sudha; Goutham, Katta Charu (International Journal of Medical Research and Review, 2017)
Aim: The purpose of the study is to compare CT only contour with MRI guided contour for delineation of the gross tumour volume (GTV) in carcinoma of rectum in external beam radiotherapy. Materials and Methods: 18patients who underwent external beam radiotherapy treatment for carcinoma rectum were selected retrospectively. For all the patients, both CT and MRI were done as a part of planning process. Two sets of GTV were generated using only CT and with MRI assistance by a single oncologist. The generated contours were then compared and quantitatively analyzed using volume analysis and dice index. Results: The CT mean GTV was larger than the MRI mean GTV volume (68.54 ± 17.56 cc for CT versus 80.95 ± 19.19 cc for MRI). The dice index value between CT only GTV and MRI assisted GTV was 0.71 ± 0.13. The comparison of GTVs showed that the GTV_MRI was comparatively small and inside the GTV_CT except for six patients for whom GTV_MRI was marginally outside the GTV_CT. Conclusion: The study showed that using MRI guidance for GTV delineation in carcinoma rectum is preferable and more accurate as compared to CT-only imaging because of superior soft tissue contrast.